Assembling bodies‐without‐organs: A poststructuralist analysis of group sex between men. (2nd November 2021) - Holmes, Dave; Hammond, Chad; Orser, Lauren; Nguyen, Huy
Abstract: Group sex among men who have sex with men may be understood as a 'radical' practice insofar as it transgresses dominant social discourses around appropriate sexual relations—prioritizing heteronormative, monogamous and risk‐averse sex. These practices are generally defined as steeped in risk, most commonly due to the potential for transmitting human immunodeficiency virus and sexually transmitted infections and accompanied by the possibility of legal and social repercussions. Our ethnographic research study explored the desires, practices and contexts of group sex participants ( n = 10) within a popular group sex party destination located in the United States. We employ a poststructuralist perspective (utilizing the work of Deleuze and Guattari) to understand group sex events with the pretext that bodies have no inherent ethics, meaning or essence: they are 'bodies without organs'. We identify group sex as a form of boundary play, in which participants pursue new limits to what their bodies can do but within a carefully constructed environment that establishes norms of interaction meant to secure trust and safety between participants. A variety of risk reduction practices are shown to be promoted and honoured within these eventful sexual(ized) spaces. The application of poststructuralist concepts of 'boundary play' and 'bodies without organs' helped to depict the construction and navigation of pleasure, safety and risk among group sex participants.